Determination of δ13C of Trace Hydrocarbons in Natural Gas Using Syringe Solid Phase Extraction (SSPE) Coupled with Gas Chromatography/Isotope Ratio Mass Spectrometry (GC/IRMS). (21st December 2019) - Yan, Cancan; Li, Zhongping; Li, Shutong; Wang, Zuodong; Xing, Lantian; Liu, Yan; Mou, Weiwei; Wang, Kaiwen
Abstract : Sample preparation technique, for the analysis of δ 13 C ratios in oil and gas samples, has gradually been recognized as one of the most crucial steps of the whole analytical process. In this study, a new convenient method, syringe solid phase extraction (SSPE), was proposed for measuring δ 13 C in natural gas samples. Based on conditional experiments of temperature and time, SSPE fitted with activated carbon adsorbent was applied with a gas chromatography/isotope ratio mass spectrometry (GC/IRMS) system for trace carbon isotope analysis. The results showed that isotopic fractionation was not clearly observed during the adsorption and desorption process, and the δ 13 C ratios measured by SSPE-GC/IRMS were in good agreement with the known δ 13 C ratios of CH4 C5 H12 measured by GC/IRMS with the accuracy all within ±0.48‰. A natural gas sample was applied to verify the efficiency of this new method, and the obtained results confirmed that SSPE-GC/IRMS is a reliable technique characterized with simplicity, efficiency, and reliability.